Dimensionality of the Raven's Advanced Progressive Matrices: Sex differences and visuospatial ability. (October 2016) - Waschl, Nicolette A.; Nettelbeck, Ted; Jackson, Simon A.; Burns, Nicholas R.
Abstract: Raven's progressive matrices are considered a measure of inductive reasoning. However, there is evidence to suggest that they are not unidimensional, and they may measure visuospatial ability in addition to inductive reasoning. We investigated the psychometric properties of several versions of the Advanced Progressive Matrices (APM). Confirmatory factor analyses and Rasch analyses were used to investigate the dimensionality of the test, sex differences regarding dimensionality, and the utility of proposed taxonomies of item solution strategies. Three samples were administered three different forms of the test. Sample 1 consisted of 1297 individuals (929 females) who completed a 12-item short form; Sample 2 consisted of 455 individuals (327 females) who completed the full APM; and Sample 3 consisted of 362 individuals (244 females) who completed a 15-item short form. Results indicated that all three forms of the APM are unidimensional and measurement invariant across sex. There was little support for the validity of the taxonomies of solution strategies. Highlights: CFA and IRT were used to examine dimensionality and sex differences in the APM. The APM tests are largely unidimensional. There are no sex differences in the latent structure of the APM tests. There is a male advantage on the latent mean of the APM.